in motor skills of s Article RETRACTED due to manipulation by the authors Exploration of Children's Motor Skills with Stunting Vs. Non-Stunting - Nuridin Widya Pranoto; Varhatun Fauziah; Arif Fadli Muchlis; Anton Komaini; Rayendra Rayendra; Nugroho Susanto; Gema Fitriady; Hendra Setyawan; Ratko Pavlovic; Alexandre Sibomana; Japhet Nadyisenga (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background: Stunting is a growth problem that occurs in children due to chronic nutrition deficiency over a long period of time. This health problem often occurs in society and is very worrying. Unfortunately, its impact on children's development is not yet fully understood. Motor skills are often associated with the children’s nutritional status. These skills are important for children as the basis for their ability to move when carrying out activities. This study aimed to evaluate differences in the motor skills of children diagnosed with stunting and non-stunting. Method: This research used a comparative approach. The sample consisted of 48 children with criteria aged 3 to 5 years. These children were divided into the stunting-diagnosed group (N=24) and the non-stunting group (N=24). Children's motor skills were measured using the TGMD-2 (Test of Gross Motor Development-2) motor skills test. The test has been tested for validity and reliability before being distributed to the participants. The Shapiro-Wilkoxon test was used to check normal data distribution. Results & Discussion: The study showed a significant difference between children diagnosed with stunting and non-stunting children by comparison (P<0.05). Children diagnosed with stunting were reported to have lower motor skills on average gross Motor Quontientx̄87. This value is below average category, while non-stunting children have Gross Motor Quontientx̄111.125, which is beyond the average category. In male  stunting children, the highest performance was in the kick movement skill with a value of ±4.25, while the lowest performance was in the gallop skill with a value of ±2.00. For girls with stunting, the highest performance was in the object control skill, striking a stationary ball with a value of ±3.53. On the other hand, the lowest performance was in the gallop skill, with a value of ±1.32. In terms of motor skills, normal boys performed better than girls in jumping, hopping, and sliding (P<0.05). For non-stunting boys, the highest performance was in hop movement skills with a value of ±7.05, while the lowest was in stationary dribble skills with a value of ±4.77. Non-stunting girls resembled the boys as the highest performance was in the locomotive hop skill with a value of ±7.67, while the lowest performance was in the underhand roll skill with a value of ±5.11. In terms of motor skills, non-stunting children performed better than stunting boys and girls (P<0.05). Conclusion: There were significant differences in motor skills between the two groups. Children diagnosed with stunting have lower motor skills compared to non-stunting children. These results provide a better understanding of the impact of stunting on children's motor development. This research also emphasizes the importance of early intervention to improve the motor skills of children diagnosed with stunting. These findings have the potential for efforts to prevent and treat stunting in children and promote the welfare of children's overall development.